Uji Antidiare Ekstrak Metanol dan Ekstrak Akuades Daun Pepaya (Carica papaya L.) terhadap Tikus Galur Wistar yang Diinduksi Oleum ricini - Naesit Andre Darvid; Husnul Khuluq; Titi Pudji Rahayu (Journal Borneo, 2023)
Diarrhea is a disease characterized by a change in the consistency of soft stool to liquid. The use of antidiarrheal drugs causes side effects such as stomach ache, nausea, or vomiting, so alternative treatments for diarrhea using natural ingredients are needed. The papaya plant (Carica papaya L.) is an herbal plant that can be used as an alternative treatment for diarrhea with fewer side effects. This study aimed to determine the antidiarrheal effect of methanol extract and aqueous extract of papaya leaves (Carica Papaya L.) on male white Wistar rats induced with Oleum ricini. This research is a laboratory experiment. The test animals were divided into 10 groups, namely negative control (CMC-Na 0.5%), positive control (Loperamide), methanol extract group, and distilled water extract with concentrations of 300, 450, and 600 mg/kgBW. Test animals were induced with Oleum ricini. The parameters observed include frequency, consistency, and weight of feces. The results of this research showed that methanol extract and distilled water at concentrations of 300 and 450 mg/kgBB were significantly able to reduce the frequency and increase the consistency of feces. Meanwhile, 300 mg/kgBB methanol extract and 600 mg/kgBB aquades extract were able to significantly reduce feces weight. The research conclusion shows that the best concentration of methanol extract and distilled water extract can have an antidiarrheal effect at concentrations of 300 mg/kgBW and 450 mg/kgBW to improve frequency and consistency. Methanol extract and distilled water extract 300 mg/kg and 600 mg/kgBW to reduce feces weight.